Strategi Pemasaran Produk UMKM Pada Era New Normal Covid-19 Di Kabupaten Luwu - Tasdin, A’zifah; Hadija, Hadija; Fianti, Anggun Thia (EXERO : Journal of Research in Business and Economics, 2024)
This study aims to determine the marketing strategy of MSME products in the new normal Covid 19 era in Luwu Regency. The results showed that the marketing strategy of MSME products in the new normal Covid 19 era in Luwu Regency, namely: increasing the variety of products offered to consumers, utilizing technology in marketing products, providing fast and good service to consumers, and conducting effective promotions.